Dectin-2 mediates phagocytosis of Lactobacillus paracasei KW3110 and IL-10 production by macrophages - Mia Yoshikawa (Nature Portfolio, 2021)
Abstract Lactic acid bacteria (LAB) are most generally used as probiotics and some strains of LAB are known to have anti-inflammatory effects. A specific strain of lactic acid bacteria, Lactobacillus paracasei KW3110 (KW3110), activates macrophages to produce interleukin-10 (IL-10), an anti-inflammatory cytokine; however, the biological mechanism remains unclear. In this study, we showed that the amount of incorporated KW3110 into a macrophage cell line, RAW 264.7, was higher than other genetically related strains using fluorescence microscopy. RNA-seq analysis indicated that treatment of macrophages with KW3110 induced Dectin-2 gene expression, which is a pattern recognition receptor, recognizing α-mannose. In addition, antibody treatment and knock down of Dectin-2, or factors downstream in the signaling pathway, decreased the amount of incorporated KW3110 and IL-10 production. Substantial lectin array analysis also revealed that KW3110 had higher binding affinities to lectins, which recognize the carbohydrate chains comprised of α-mannose, than two other LAB. In conclusion, KW3110 is readily incorporated into macrophages, leading to IL-10 production. Dectin-2 mediated the phagocytosis of KW3110 into macrophages and this may be involved with the characteristic carbohydrate chains of KW3110.